Dynamical Analysis and Simulation Validation of Incompletely Restrained Cable-Suspended Swinging System Driven by Two Cables - Naige Wang; Guohua Cao; Zhencai Zhu; Weihong Peng (Shock and Vibration)
The flexibility of the suspension multicables and driven length difference between two cables cause the translation and rotation of the platform in the incompletely restrained cable-suspended system driven by two cables (IRCSWs2), which are theoretically investigated in this paper. The suspension cables are spatially discretized using the assumed modes method (AMM) and the equations of motion are derived from Lagrange equations of the first kind. Considering all the geometric matching conditions are approximately linear with external actuator, the differential algebraic equations (DAEs) are transformed to a system of ordinary differential equations (ODEs). Using linear boundary conditions of the suspension cable, the current method can obtain not only the accurate longitudinal displacements of cable and posture of the platform, but also the tension between the platform and cables, and the current method is verified by ADAMS simulation.